Concept Review E motivation in the literature of physical rehabilitation (Cuestiones de Fisioterapia, 2005)
The present study analyses the conception concerning the concept of motivation in the literature. Motivation is required in all learning processes. To motivate a patient is probably one of the most important and difficult tasks that health professionals have to face. To compile all the factors that might influence the motivation and to review the strategies considered to be valid to stimulate a patient is the main goal of the article. A review about all the psychological theories concerning motivation and the interpretation of this term in the literature of physical rehabilitation was carried out. For that reason, several databases in internet were used. Medline, PubMed, Pedro, Elsevier were the selected databases, using motivation», «rehabilitation» and «frontal lobe» as keywords. Besides, a manual search in Satakunta Polytechnic library in Pori was carried out. Motivation has a neurophysiological basis on the limbic system. Besides, motivation may be as¬essed based on very different philosophical theories, such as Individualism or «Self-Determina-tion» theory. Therefore, depending on the approach, the analysis of the circumstances may differ absolutely. To understand the motivation as influenced by internal aspects of the human being plus external factors is the best manner to reach a unified idea of this term. Patients, professionals and family interests have to be taking into account to get an agreement.